Career and Professional Satisfaction of Oral and Maxillofacial Surgery Residents, Academic Surgeons, and Private Practitioners: Does Gender Matter?. Issue 1 (1st January 2017) - Marti, Kyriaki C.; Lanzon, Jesse; Edwards, Sean P.; Inglehart, Marita R.
Abstract : The aims of this study were to determine whether male vs. female oral and maxillofacial surgery (OMS) residents, academic surgeons (i.e., faculty members), and private practitioners in the U.S. differed in their general career satisfaction and job/professional satisfaction. Survey data were collected in 2011–12 from 267 OMS residents (response rate 55%), 271 OMS academic surgeons (response rate 31%), and 417 OMS private practitioners (response rates 13% web‐based survey and 29% postal mail survey). The results showed that while the male vs. female OMS private practitioners and academic surgeons did not differ in their career satisfaction, the female residents had a lower career satisfaction than the male residents (on four‐point scale with 4=most satisfied: 3.03 vs. 3.65; p<0.01). The male vs. female OMS private practitioners and academic surgeons also did not differ in their job satisfaction. However, the female residents agreed on average less that they were able to practice OMS in the way they want, felt less proud to be an oral and maxillofacial surgeon, were less satisfied with their career, and were more likely to consider a career change in the next five years than the male residents. While these male and female oral and maxillofacial surgeons in private practice and academia did not differ in their career and job satisfaction, the male and female residents differed significantly, with female residents reporting a significantly poorer career and job satisfaction than male residents. Future research needs to explore ways to improve career and professional satisfaction of female OMS residents.